Actividad insulino-mimética del Vanadio - Pacheco Calderón, Javier (2006)
Diabetes mellitus is a serious chronic metabolic disordercharacterized by an increased plasma glucose concentrationand vascular and neurologic complications as well. Diabetesmellitus results from relative or absolute deficiency of insulinsecretion or insulin deficient action. Although there are anumber of oral antidiabetic agents besides insulin or insulinanalogues, none of them is optimal.Vanadium can mimic insulin effects in vitro and in vivoand the possibility of using vanadium compounds asantidiabetic agents is under study. This review will summarizethe insulin mimetic action of vanadium and its possiblemechanisms in comparison with insulin.